ANALISIS PENERAPAN ISTIHSAN (BI AL-MASLAHAH) DALAM KONSEP WASIAT WAJIBAH DI INDONESIA - Elin Herlina; Sahril Sidik; Usep Saepullah (USRAH: Jurnal Hukum Keluarga Islam, 2026)
This study aims to fill this gap by analyzing the methodological construction of "Dual-Layered Istihsan" in the Compilation of Islamic Law (KHI) as a response to the rigidity of standard qiyas jaliy which blocks the grandchildren’s rights (mahjub). Using a normative juridical approach with usul fiqh analysis, Previous studies on the inheritance rights of orphaned grandchildren tend to discuss Substitute Heirs and Mandatory Bequests separately or merely as positive legal policies. this study reveals a novelty that KHI does not merely apply a single form of istihsan, but rather establishes a Dual-Layered Protection Mechanism. First, Article 185 (Substitute Heirs) is positioned as the primary solution applying pure istihsan bi al-maslahah to grant full heir status. Second, Article 209 (Mandatory Bequest) functions as a safety net, representing a hybridization of istihsan bi al-nass and bi al-maslahah for relatives excluded from the first mechanism. This study concludes that the dialectic between these two articles proves that KHI prioritizes substantive justice (maqasid al-syari'ah) over classical legal formalism without dismantling the fundamental structure of fara'id